Nonsurgical treatment and stability of an adult with a severe anterior open-bite malocclusion - Aldo Otazú Cambiano; Guilherme Janson; Diego Coelho Lorenzoni; Daniela Gamba Garib; Dino Torres Dávalos (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVES: A skeletal anterior open-bite is a challenging malocclusion for the orthodontist due to the difficulty and instability of correction. Treatment options for the adult patient include extractions, anterior extrusion with intermaxillary elastics, posterior intrusion using skeletal anchorage, occlusal adjustment, and orthognathic surgery. Patient compliance plays a key role in posttreatment stability. The present case report demonstrates the orthodontic treatment of an adult patient who presented with a complex open-bite malocclusion. MATERIALS AND METHODS: Treatment involved the placement of four miniscrews to assist intrusion of maxillary molars by applying posterior vertical maxillary elastics and extrusion of the anterior segments using anterior vertical interarch elastics. RESULTS: Ideal intercuspation was successfully achieved and good stability was maintained during 3 years following treatment. CONCLUSION: The intrusion of the maxillary molars with miniscrews is an interesting option in selected cases of skeletal anterior open bite. The retention protocol should be specific in these cases.